Relationship between the Behavior of Patients with Tuberculosis and the Health Literacy of Mashhad Caregivers - Parisa Ramezannia; Mohammad Vahedian Shahroudi; Hadi Tehrani; Habibollah Esmaili (Fasa University of Medical Sciences, 2020)
Background & Objective: Health-promoting behavior and health literacy is one of the main determinants of health and benefiting from them can increase health behaviors and improve access to health care. The aim of this study was to investigate the relationship between the behavior of patients with tuberculosis and the health literacy of their caregivers in Mashhad. Materials & Methods: This descriptive study was performed in 2010 on 90 patients with tuberculosis and 90 caregivers per patient in Mashhad. Multi-stage sampling was used for sampling. Data were collected using a personal information questionnaire and a researcher-made questionnaire to assess patients' behavior. Data were analyzed using SPSS software version 16 and descriptive and inferential statistical tests (Spearman correlation and regression and Mann-Whitney and Kruskal varicose veins). The significance level was considered at P<0.05. Results: The relationship between tuberculosis prevention behaviors and caregivers' health literacy was significant, so people with higher health literacy levels showed more preventive behaviors. Therefore, it is necessary to pay more attention to health literacy in health promotion programs and increase preventive behaviors. Conclusion: There was a significant relationship between tuberculosis prevention behaviors and the health literacy of caregivers. Therefore, it is necessary to pay more attention to health literacy in health promotion programs and increase preventive behaviors.